2019
DOI: 10.3390/ijms20246263
|View full text |Cite
|
Sign up to set email alerts
|

The Eighth ECS Workshop on “Calcium Signaling in Aging and Neurodegenerative Diseases”

Abstract: The European Calcium Society (ECS) is very glad to present the realization of a special issue of the International Journal of Molecular Sciences (IJMS) related to the eighth ECS workshop organized this year around the theme of “Calcium Signaling in Aging and Neurodegenerative Diseases” [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Strong evidence supports the involvement of intracellular Ca 2+ dyshomeostasis in aging and neurodegenerative disorders including AD ( 19 ). Our group, and others, have recently shown that long-term cultures of rat hippocampal neurons display characteristics of aged neurons ( 20 22 ).…”
Section: Tlr4 and Calcium Signaling In Alzheimer’s Diseasementioning
confidence: 78%
“…Strong evidence supports the involvement of intracellular Ca 2+ dyshomeostasis in aging and neurodegenerative disorders including AD ( 19 ). Our group, and others, have recently shown that long-term cultures of rat hippocampal neurons display characteristics of aged neurons ( 20 22 ).…”
Section: Tlr4 and Calcium Signaling In Alzheimer’s Diseasementioning
confidence: 78%
“…In the last few years, a large body of evidence indicates that changes in intracellular Ca 2+ homeostasis may contribute to neuron damage in AD and PD. [156] Early evidence suggested that neurons obtained from mouse models of AD displayed changes in intracellular Ca 2+ homeostasis, including alterations in resting levels of intracellular Ca 2+ and Ca 2+ stores. [157] These changes could be associated to the effects of mutations in the APP and presenilins PS1 and PS2, which process APP either directly or indirectly via excessive production of Aβ species.…”
Section: Ca 2+ Dysregulation and Downstream Effects In Alzheimer's Di...mentioning
confidence: 99%